California and the Future of Public Higher Education - Marginson, Simon (International Higher Education, 2015)
The California Master Plan for Higher Education, which combined high quality research universities with access-based community colleges in a system differentiated by institutional mission, has been influential worldwide. But in a low tax state, the access element of the Plan has now hit the wall.